Profitability and disposal pattern of milk in underdeveloped hill production system of Meghalaya - FEROZE, S M; SINGH, RAM; SIROHI, SMITA (The Indian Journal of Animal Sciences, 2016)
Though dairy is regarded as integral part of a farm in the country and contributes significantly to the rural economy, the situation in the North Eastern hills is considered to be different as the production system is underdeveloped. Hence, this article tried to assess the profitability and disposal pattern of milk in Meghalaya state in the North Eastern Hills of India. A sample of farmers (300) from two districts i.e., East Khasi Hills and Ri-Bhoi was drawn randomly. The study reveals that though the net return from local was negative, the cross bred animals are highly profitable. The farmers of the state either sell the milk to the consumers directly or to the co-operative societies. Hence, it is suggested that the rearing of CB animals should be encouraged in the hill region which is considered to be underdeveloped production system.